Method for manufacturing lithium secondary battery comprising lithium-rich manganese-based oxide

By charging in a constant current-constant voltage mode under pressure, the lithium-rich manganese oxide lithium secondary battery has been solved by solving the problem of oxygen desorption and gas generation during the high-pressure activation process, and the effect of suppressing abnormal capacity increase and gas generation is achieved, and the stability and life of the battery are improved.

CN119816985APending Publication Date: 2025-04-11LG ENERGY SOLUTION LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380063805.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-23
Filing Date
2023-12-20
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

During the high-pressure activation process, lithium-rich manganese oxide lithium secondary batteries are prone to oxygen desorption, resulting in excessive gas and manganese transition metal dissolution, resulting in abnormal increase in capacity and gas generation.

Method used

The activation step under certain conditions, including charging in a constant current mode under pressure until the charging cutoff voltage, and then charging in a constant voltage mode, with a charging cutoff voltage greater than 4.35 V, to suppress abnormal capacity increase and gas generation.

Benefits of technology

It effectively suppresses abnormal capacity increase and gas generation during battery operation, and improves the battery's operating stability and life characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119816985A_ABST
    Figure CN119816985A_ABST
Patent Text Reader

Abstract

The present invention relates to a method for manufacturing a lithium secondary battery, the method comprising the steps of: preparing a battery cell comprising a positive electrode, a negative electrode, and an electrolyte, in which the positive electrode contains a lithium-rich manganese-based oxide, the manganese content is greater than 50 mol% with respect to all metals other than lithium, and the electrolyte content is greater than 50 mol% with respect to all metals other than lithium; and the ratio of the number of moles of lithium to the number of moles of all metals other than lithium (Li / Me) is greater than 1; and charging and discharging the battery cell under voltage to activate the battery, in which, in the activation step, charging is performed in a constant current mode up to a charge-off voltage, which is greater than 4.35 V, and then charging is performed in a constant voltage mode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of priority from Korean Patent Application No. 10-2022-0183684 filed in the Korean Intellectual Property Office on December 23, 2022, the disclosure of which is incorporated herein by reference in its entirety.

[0003] The present invention relates to a method for manufacturing a lithium secondary battery containing a lithium-rich manganese-based oxide, and more particularly, to a method for manufacturing a lithium secondary battery containing a lithium-rich manganese-based oxide that can suppress abnormal capacity increase and gas generation during battery operation. Background Art

[0004] Lithium secondary batteries are energy storage media that have been used in various fields since they were commercialized in 1991. As the market for products equipped with lithium secondary batteries expands, research on improving the energy density of lithium secondary batteries has been actively conducted. One of the most notable methods is to develop a positive electrode active material with a composition that can utilize a larger amount of lithium than before.

[0005] As positive electrode active materials that can utilize a larger amount of lithium, lithium-rich transition metal oxides having a layered structure and a molar ratio of lithium to transition metal greater than 1 have been developed. Since such lithium-rich transition metal oxides achieve capacity by simultaneously utilizing the cationic redox reaction of the transition metal and the anionic redox reaction using oxygen in the positive electrode structure, they cannot obtain high capacity. Typical lithium-rich transition metal oxides currently being actively studied include lithium-rich manganese oxides having a molar ratio of lithium to transition metal greater than 1 and a manganese content of more than 50 mol % in all transition metals. The lithium-rich manganese oxide has the following structure: LiMO2 (wherein M is a transition metal) having a layered structure is mixed with Li2MnO3 having a rock salt structure, and the activation process is performed at a high pressure of more than 4.4 V, so that Li2MnO3 can be activated to achieve high capacity. However, the problem is that during this high-pressure activation process, oxygen desorption occurs, thereby generating excess gas, and dissolution of transition metals such as manganese occurs. Lowering the activation voltage can reduce the amount of gas generated during the activation process, but in this case, this causes problems such as activation of residual Li2MnO3 phase in the crystal structure, abnormal behavior resulting in an abnormal increase in capacity, and generation of additional gas during battery operation. Summary of the invention

[0006] Technical issues

[0007] The present invention has been made to solve the above-mentioned problems, and therefore, an object of the present invention is to provide a method for manufacturing a lithium secondary battery using a lithium-rich manganese-based oxide, which can suppress abnormal capacity increase and gas generation during battery operation by activation under specific conditions.

[0008] Technical Solution

[0009] According to the present invention, there is provided a method for manufacturing a lithium secondary battery, the method comprising the following steps:

[0010] Preparing a battery cell including a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode contains a lithium-rich manganese-based oxide, wherein the content of manganese relative to all metals other than lithium is greater than 50 mol %, and the ratio of the number of moles of lithium to the number of moles of all metals other than lithium (Li / Me) is greater than 1; and

[0011] Charge and discharge the battery cells under pressure to activate the battery.

[0012] In the activation step, charging is performed in a constant current mode until a charge cut-off voltage is reached, and then charging is performed in a constant voltage mode, wherein the charge cut-off voltage is greater than 4.35 V.

[0013] The constant current mode charging may be performed to include at least a portion of the potential plateau interval occurring during the constant current mode charging, and the cutoff current during the constant voltage mode charging may be 0.01C to 0.5C.

[0014] In one embodiment, during the activation step, constant current mode charging may be performed from SOC 60 to SOC 100 .

[0015] Alternatively, in another embodiment, in the activation step, charging may include: a first charging step: constant current charging at a first current rate, and a second charging step: constant current charging at a second current rate different from the first current rate, and then constant voltage charging. The first current rate and the second current rate may be independently 0.1 C to 1.0 C.

[0016] The first charging step may be performed until the SOC of the battery cell reaches 30 to 60, and the second charging step may be performed after the first charging step, ie, from SOC 30 to 60 to SOC 90 to 100.

[0017] On the other hand, it is preferred that the activation step be performed while the battery cell is mounted on a jig and pressurized.

[0018] In addition, the activation step can be carried out while changing the pressurization pressure. For example, the activation step can include charging at a pressurization pressure P1 until the SOC of the battery cell reaches 10 to 20, and then performing charge and discharge at a pressurization pressure P2. The pressurization pressure P1 and the pressurization pressure P2 can satisfy the following mathematical formula (1).

[0019] Mathematical formula (1): 5P1 ≤ P2 ≤ 15P1

[0020] On the other hand, in the present invention, when the charging curve area in the voltage range of 4.3 V to 4.6 V in the dQ / dV graph obtained by differentiating the graph of the voltage V measured while charging the battery cell to 4.6 V is represented as A, and the charging curve area in the range of 4.3 V to the charging cut-off voltage in the dQ / dV graph obtained by differentiating the graph of the voltage V measured while charging the battery cell to the charging cut-off voltage of the activation step is represented as B, it is preferably satisfied with the following mathematical formula (2).

[0021] Mathematical formula (2): 0.5A ≤ B ≤ A

[0022] In the present invention, the lithium-rich manganese-based oxide can be represented by the following Chemical Formula 1.

[0023] [Chemical Formula 1]

[0024] Li a Ni b Co c Mn d M e O2

[0025] Wherein, in Chemical Formula 1,

[0026] 1 < a, 0 ≤ b ≤ 0.5, 0 ≤ c ≤ 0.1, 0.5 ≤ d < 1.0 and 0 ≤ e ≤ 0.2,

[0027] M can include at least one selected from Al, B, Co, W, Mg, V, Ti, Zn, Ga, In, Ru, Nb, Sn, Sr, and Zr,

[0028] preferably 1.1 ≤ a ≤ 1.5, 0.1 ≤ b ≤ 0.4, 0 ≤ c ≤ 0.05, 0.5 ≤ d ≤ 0.80 and 0 ≤ e ≤ 0.1. Brief Description of the Drawings

[0029] Figure 1 is a graph showing the cycle characteristics of the lithium secondary battery activated by the methods of Examples 1 to 3 and Comparative Examples 1 to 4. Detailed Description of the Invention

[0030] The terms or words used in the specification and the appended claims should not be construed as being limited to the ordinary meaning or dictionary meaning, and the present invention should be interpreted with meanings and concepts consistent with the technical spirit of the present invention based on the principle that inventors can appropriately define the concepts of the terms in order to describe their own inventions in the best manner.

[0031] In the present invention, "primary particles" refer to particle units that appear to have no particle boundaries when observed under a field of view at a magnification of 5,000 to 20,000 times using a scanning electron microscope. "Average particle size of primary particles" refers to the arithmetic mean value calculated after measuring the particle size of primary particles observed in a scanning electron microscope image.

[0032] In the present invention, "secondary particles" are particles formed by agglomeration of a plurality of primary particles.

[0033] In the present invention, the average particle size D 50 " means the particle size at which the cumulative volume of powder particles (eg, positive electrode active material, negative electrode active material, etc.) reaches 50% in the particle size distribution curve of the particles. Laser diffraction can be used to measure D 50 It can be measured by a method comprising the following steps: dispersing a powder of the particles to be measured in a dispersion medium, introducing it into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT 3000), irradiating it with ultrasound at about 28 kHz at an output power of 60 W to obtain a volume cumulative particle size distribution, and determining the particle size corresponding to 50% of the cumulative volume.

[0034] In the present invention, "SOC X" refers to a state in which the percentage of charge capacity relative to discharge capacity in a battery cell (ie, (charge capacity of the battery cell in the voltage range of 4.6 V to 2.0 V / discharge capacity)×100) is X, which occurs when the battery cell is discharged from 4.6 V to 2.0 V.

[0035] The present inventors have conducted repeated studies to improve the phenomenon of abnormal capacity increase and increased gas generation during the operation of lithium secondary batteries using lithium-rich manganese oxides. As a result, they found that this phenomenon can be improved by performing an activation step under specific conditions when manufacturing lithium secondary batteries, and completed the present invention.

[0036] The present invention will be described in detail below.

[0037] The method for manufacturing a lithium secondary battery according to the present invention comprises:

[0038] (1) a step of preparing a battery cell including a positive electrode, a negative electrode and an electrolyte, and

[0039] (2) a step of charging and discharging the battery cells under pressure to activate the battery,

[0040] In the activation step, charging is performed in a constant current mode until a charge cut-off voltage is reached, and then charging is performed in a constant voltage mode, wherein the charge cut-off voltage is greater than 4.35 V.

[0041] (1) Steps for preparing battery cells

[0042] First, a battery cell including a positive electrode, a negative electrode, and an electrolyte is prepared.

[0043] For example, a battery cell may be manufactured by forming an electrode assembly including a positive electrode and a negative electrode, placing the electrode assembly in a battery case, and then injecting an electrolyte to seal the battery case. At this time, the electrode assembly may include a separator between the positive electrode and the negative electrode.

[0044] The electrode assembly may be various forms of electrode assemblies well known in the art, such as a jelly-roll type, a stack type, a stacked laminate type, or a stacked folded type electrode assembly, and there is no particular limitation on the form thereof.

[0045] The jellyroll type electrode assembly may be manufactured by inserting a sheet-shaped separator between a sheet-shaped positive electrode and a sheet-shaped negative electrode and then winding them in one direction.

[0046] The stacked electrode assembly can be manufactured by cutting the positive electrode, the separator, and the negative electrode into desired shapes and then stacking the cut positive electrode / separator / negative electrode in sequence.

[0047] The stacked laminate type electrode assembly may be manufactured by stacking a positive electrode, a separator, and a negative electrode to manufacture a plurality of unit cells, stacking the plurality of unit cells with a separator interposed therebetween, and then laminating them by a method such as heating.

[0048] The stacked folding type electrode assembly may be manufactured by stacking a positive electrode, a separator, and a negative electrode to manufacture a plurality of unit cells, arranging the plurality of unit cells on one surface or both surfaces of a long folding separator, and then winding the folding separator.

[0049] On the other hand, as the battery case, various battery cases known in the art, such as a cylindrical battery case, a prismatic battery case, a pouch-type battery case, etc., may be used, and the type thereof is not particularly limited.

[0050] On the other hand, the positive electrode according to the present invention includes a positive electrode active material, and the positive electrode active material includes a lithium-rich manganese-based oxide, wherein the content of manganese is greater than 50 mol% relative to all metals other than lithium, and the molar ratio of lithium to all metals other than lithium (Li / Me) is greater than 1. Specifically, the positive electrode according to the present invention includes a positive electrode current collector and a positive electrode active material layer formed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer includes a lithium-rich manganese-based oxide, and the molar ratio of lithium to all metals other than lithium (Li / Me) is greater than 1.

[0051] In the case of a lithium-rich manganese-based oxide containing excess lithium, it has a structure in which a layered phase (LiM'O2) is mixed with a rock salt phase (Li2MnO3). During the initial activation process, the rock salt phase is activated, and excess lithium ions are generated, thereby achieving a high capacity.

[0052] Preferably, the lithium-rich manganese-based oxide can be represented by the following Chemical Formula 1.

[0053] [Chemical Formula 1]

[0054] Li a Ni b Co c Mn d M e O2

[0055] Wherein, in Chemical Formula 1, M can be at least one selected from Al, B, Co, W, Mg, V, Ti, Zn, Ga, In, Ru, Nb, Sn, Sr, and Zr.

[0056] On the other hand, a is the molar ratio of Li in the lithium-rich manganese-based oxide, and can be 1 < a, 1.1 ≤ a ≤ 1.5, or 1.1 ≤ a ≤ 1.3. When a is within the above range, the irreversible capacity of the silicon-based negative electrode active material can be sufficiently compensated, and high-capacity characteristics can be achieved.

[0057] b is the molar ratio of Ni in the lithium-rich manganese-based oxide, and can be 0 ≤ b ≤ 0.5, 0.1 ≤ b ≤ 0.4, or 0.2 ≤ b ≤ 0.4.

[0058] c is the molar ratio of Co in the lithium-rich manganese-based oxide, and can be 0 ≤ c ≤ 0.1, 0 ≤ c ≤ 0.08, or 0 ≤ c ≤ 0.05. If c exceeds 0.1, it is difficult to ensure a high capacity, gas generation and deterioration of the positive electrode active material become aggravated, and the life characteristics may deteriorate.

[0059] d is the molar ratio of Mn in the lithium-rich manganese-based oxide, and may be 0.5≤d<1.0, 0.50≤d≤0.80, or 0.50≤d≤0.70. If d is less than 0.5, the proportion of the rock salt phase becomes too small, and thus the effects of negative electrode irreversible compensation and capacity improvement are slight.

[0060] e is a molar ratio of the doping element M in the lithium-rich manganese-based oxide, and may be 0≤e≤0.2, 0≤e≤0.1, or 0≤e≤0.05. If the content of the doping element is too high, it may have an adverse effect on the capacity of the active material.

[0061] On the other hand, in the lithium-rich manganese oxide represented by [Chemical Formula 1], the ratio of the mole number of Li to the mole number of all metal elements except Li (Li / Me) can be 1.2 to 1.5, 1.25 to 1.5 or 1.25 to 1.4. When the Li / Me ratio satisfies the above range, excellent rate characteristics and capacity characteristics can be exhibited. If the Li / Me ratio is too high, the conductivity may decrease and the rock salt phase (Li2MnO3) may increase, thereby increasing the degradation rate. If the Li / Me ratio is too low, the effect of improving the energy density is slight.

[0062] On the other hand, the composition of the lithium-rich manganese-based oxide can be represented by the following [Chemical Formula 2].

[0063] [Chemical formula 2]

[0064] X Li2MnO3·(1-X)Li[Ni 1-y-z-w Mn y Co z M w ]O2

[0065] In [Chemical Formula 2], M may be at least one metal ion selected from Al, B, Co, W, Mg, V, Ti, Zn, Ga, In, Ru, Nb, Sn, Sr, and Zr.

[0066] X refers to the ratio of the Li2MnO3 phase in the lithium-rich manganese-based oxide, and can be 0.2≤X≤0.5, 0.25≤X≤0.5, or 0.25≤X≤0.4. When the ratio of the Li2MnO3 phase in the lithium-rich manganese-based oxide satisfies the above range, the irreversible capacity of the silicon-based negative electrode active material can be fully compensated, and high capacity characteristics can be achieved.

[0067] y is a molar ratio of Mn in the LiM'O2 layer, and may be 0.4≤y<1, 0.4≤y≤0.8, or 0.4≤y≤0.7.

[0068] z is a molar ratio of Co in the LiM'O2 layer, and may be 0≤z≤0.1, 0≤z≤0.08, or 0≤z≤0.05. If z is greater than 0.1, gas generation and degradation of the positive electrode active material may become more severe, and life characteristics may deteriorate.

[0069] w is the molar ratio of the doping element M in the LiM'O2 layer, and may be 0≤w≤0.2, 0≤w≤0.1, or 0≤w≤0.05.

[0070] On the other hand, if necessary, the positive electrode active material according to the present invention may further include a coating on the surface of the lithium-rich manganese oxide. When the positive electrode active material includes the coating, the coating inhibits the contact between the lithium-rich manganese oxide and the electrolyte and reduces the side reaction of the electrolyte, thereby obtaining an effect of improving the life characteristics.

[0071] The coating may include a coating element M 1 , coating element M 1 The coating element M may be, for example, at least one selected from the group consisting of Al, B, Co, W, Mg, V, Ti, Zn, Ga, In, Ru, Nb, Sn, Sr, and Zr, preferably Al, Co, Nb, W, and combinations thereof, more preferably Al, Co, and combinations thereof. 1 Two or more types may be included, for example, Al and Co.

[0072] The coating element can be in the form of an oxide, i.e., M 1 Oz (1≤z≤4) exists in the coating.

[0073] The coating layer can be formed by methods such as dry coating, wet coating, chemical vapor deposition (CVD), physical vapor deposition (PVD) and atomic layer deposition (ALD). Among them, formation by atomic layer deposition is preferred because a coating layer having a wider area can be formed.

[0074] Based on the total surface area of ​​the lithium-rich manganese oxide particles, the coating layer may be formed in an area of ​​10% to 100%, preferably 30% to 100%, and more preferably 50% to 100%. When the coating layer is formed in an area satisfying the above range, the effect of improving the life characteristics is excellent.

[0075] On the other hand, the positive electrode active material according to the present invention may be in the form of secondary particles in which a plurality of primary particles are agglomerated, and the average particle size D of the secondary particles is 50 The diameter of the positive electrode active material may be 2 μm to 10 μm, preferably 2 μm to 8 μm, and more preferably 4 μm to 8 μm. 50 When the above range is satisfied, excellent electrode density can be achieved, and degradation of capacity and rate characteristics can be minimized.

[0076] In addition, the BET specific surface area of ​​the positive electrode active material can be 1 m 2 / g to 10 m 2 / g, 3 to 8 m 2 / g or 4 to 6m 2 / g. If the BET specific surface area of ​​the positive electrode active material is too low, the reaction area with the electrolyte is insufficient, making it difficult to achieve sufficient capacity. If the specific surface area is too high, water absorption is rapid and the side reaction with the electrolyte is accelerated, making it difficult to ensure life characteristics.

[0077] On the other hand, the lithium-rich manganese-based oxide can be produced by mixing a transition metal precursor and a lithium raw material and then firing the mixture.

[0078] As lithium raw materials, for example, lithium-containing carbonates (such as lithium carbonate, etc.), hydrates (such as lithium hydroxide hydrate (LiOH·H2O), etc.), hydroxides (such as lithium hydroxide, etc.), nitrates (such as lithium nitrate (LiNO3)), etc.), chlorides (such as lithium chloride (LiCl)), etc. can be used, among which a single type or a mixture of two or more types can be used.

[0079] On the other hand, the transition metal precursor may be in the form of a hydroxide, an oxide or a carbonate. When the carbonate form of the precursor is used, it is more preferred that a positive electrode active material having a relatively high specific surface area can be produced.

[0080] The transition metal precursor can be prepared by a coprecipitation method. For example, the transition metal precursor can be prepared by dissolving each raw material containing transition metal in a solvent to prepare a metal solution, then mixing the metal solution, an ammonium cation complex forming agent and an alkaline compound, and performing a precipitation reaction. In addition, if necessary, an oxidant or oxygen can also be added during the coprecipitation reaction.

[0081] At this time, the raw material containing transition metals can be acetates, carbonates, nitrates, sulfates, halides, sulfides, etc. of each transition metal. Specifically, the raw material containing transition metals can be NiO, NiCO3·2Ni(OH)2·4H2O, NiC2O2·2H2O, Ni(NO3)2·6H2O, NiSO4, NiSO4·6H2O, Mn2O3, MnO2, Mn3O4, MnCO3, Mn(NO3)2, MnSO4·H2O, manganese acetate, manganese halide, cobalt sulfate, cobalt nitrate, cobalt carbonate, cobalt oxide, cobalt acetate, cobalt halide, etc.

[0082] The ammonium cation complex forming agent may be at least one selected from NH4OH, (NH4)2SO4, NH4NO3, NH4Cl, CH3COONH4 and (NH4)2CO3.

[0083] The basic compound can be at least one selected from NaOH, Na2CO3, KOH and Ca(OH)2. The form of the precursor can vary depending on the type of basic compound used. For example, when NaOH is used as the basic compound, the hydroxide form of the precursor can be obtained, and when Na2CO3 is used as the basic compound, the carbonate form of the precursor can be obtained. In addition, when the basic compound and the oxidant are used together, the oxide form of the precursor can be obtained.

[0084] On the other hand, the transition metal precursor and the lithium raw material are mixed in an amount such that the molar ratio of total transition metal (Ni+Co+Mn):Li is 1:1.05 to 1:2, preferably 1:1.1 to 1:1.8, and more preferably 1:1.25 to 1:1.8.

[0085] On the other hand, firing can be carried out at a temperature of 600° C. to 1000° C. or 700° C. to 950° C., and the firing time can be 5 hours to 30 hours or 5 hours to 20 hours. In addition, the firing atmosphere can be an air atmosphere or an oxygen atmosphere, for example, an atmosphere containing 20 volume % to 100 volume % oxygen.

[0086] On the other hand, the positive electrode active material layer may further include a conductive material and a binder in addition to the positive electrode active material.

[0087] Examples of conductive materials include spherical or flaky graphite; carbon materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber, single-walled carbon nanotubes, and multi-walled carbon nanotubes; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, etc. Among them, a single type or a mixture of two or more types can be used. Based on the total weight of the positive electrode active material layer, the content of the conductive material can be 0.1 wt % to 20 wt %, 1 wt % to 20 wt %, or 1 wt % to 10 wt %.

[0088] In addition, the binder may include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber (EPDM rubber), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber and various copolymers thereof. Among them, a single type or a mixture of two or more types can be used. Based on the total weight of the positive active material layer, the content of the binder may be 1 wt % to 20 wt %, 2 wt % to 20 wt % or 2 wt % to 10 wt %.

[0089] Next, the negative electrode may include, for example, a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector. The negative electrode active material layer may optionally include a binder and a conductive material as well as the negative electrode active material.

[0090] There is no particular restriction on the negative electrode current collector, as long as it has high conductivity and does not cause chemical changes in the battery, and for example, copper, stainless steel, aluminum, nickel, titanium, fired carbon, or copper or stainless steel treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used. In addition, the thickness of the negative electrode current collector can generally be 3 μm to 500 μm. In addition, similar to the positive electrode current collector, the negative electrode current collector can be formed with fine concave-convex on its surface to enhance the adhesion of the negative electrode active material. For example, the negative electrode current collector can be used in different forms, such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabric structures.

[0091] As the negative electrode active material, a compound capable of reversibly inserting and deinserting lithium can be used. Specific examples of the negative electrode active material may include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber or amorphous carbon; (semi)metallic materials capable of forming an alloy with lithium, such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloy, Sn alloy or Al alloy; (semi)metallic oxides capable of doping and dedoping lithium, such as SiO β (0<β<2), SnO2, vanadium oxide and lithium vanadium oxide; composite materials containing (semi)metallic materials and carbonaceous materials, such as Si-C composite materials or Sn-C composite materials, and any one of them or a mixture of two or more thereof can be used.

[0092] In addition, a metallic lithium film can be used as a negative electrode active material. In addition, low-crystalline carbon and high-crystalline carbon can be used as carbon materials. Typical examples of low-crystalline carbon include soft carbon and hard carbon. Typical examples of high-crystalline carbon include irregular, plate-like, flaky, spherical or fibrous natural graphite or artificial graphite, condensed graphite, pyrolytic carbon, mesophase pitch-like carbon fibers, mesophase carbon microbeads, high-temperature sintered carbon such as mesophase pitch and coke derived from petroleum or coal tar pitch.

[0093] The conductive material is used to impart conductivity to the electrode, and the conductive material can be used without particular limitation as long as it has electronic conductivity and does not cause chemical changes in the constructed battery. Specific examples thereof include: graphite, such as natural graphite and artificial graphite; carbon materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber and carbon nanotubes; metal powders or metal fibers such as copper, nickel, aluminum and silver; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; or conductive polymers, such as polyphenylene derivatives, and any single type or a mixture of two or more types thereof can be used. Based on the total weight of the negative electrode active material layer, the content of the conductive material can generally be 1% to 30% by weight, preferably 1% to 20% by weight, and more preferably 1% to 10% by weight.

[0094] The binder improves the adhesion between the negative electrode active material particles and the adhesion between the negative electrode active material and the negative electrode collector. Its specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-co-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber or its various copolymers, and any single type or a mixture of two or more types thereof can be used. Based on the gross weight of the negative electrode active material layer, the content of the binder can be 1% by weight to 30% by weight, preferably 1% by weight to 20% by weight, more preferably 1% by weight to 10% by weight.

[0095] The negative electrode active material layer can be prepared by applying a negative electrode slurry containing a negative electrode active material and optionally a binder and a conductive material onto a negative electrode collector and drying the applied slurry, or can be prepared by casting the negative electrode slurry on a separate support and then laminating a film peeled off from the support on a current collector.

[0096] Next, the separator separates the negative electrode and the positive electrode from each other and provides a mobile channel for lithium ions. The separator can be used without particular restriction as long as it is used as a separator in a typical lithium secondary battery. In particular, it is preferred that the separator has low resistance to the ion migration of the electrolyte and has excellent ability to impregnate the electrolyte. Specifically, the separator can be a porous polymer film, such as a porous polymer film formed by a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer and an ethylene / methacrylate copolymer, or a laminated structure of more than two layers thereof. In addition, a typical porous non-woven fabric can be used, such as a non-woven fabric made of glass fiber, polyethylene terephthalate fiber, etc. with a high melting point. In addition, in order to ensure heat resistance or mechanical strength, a coated separator containing a ceramic component or a polymer material can be used, and can be optionally used as a single layer or multilayer structure.

[0097] Next, the electrolyte used herein may include various electrolytes that can be used in lithium secondary batteries, such as organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, molten inorganic electrolytes, or combinations thereof, and there is no particular limitation on the type thereof.

[0098] For example, the electrolyte may include an organic solvent and a lithium salt.

[0099] The organic solvent may be used without any particular limitation, as long as it is used as a medium through which ions participating in the electrochemical reaction of the battery can migrate. Specific examples of the organic solvent may include ester solvents such as methyl acetate, ethyl acetate, γ-butyrolactone or ε-caprolactone; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene or fluorobenzene; carbonate solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC) or propylene carbonate (PC); alcohol solvents such as ethanol or isopropanol; nitrile such as R-CN (wherein R is a linear, branched or cyclic hydrocarbon group having 2 to 20 carbon atoms, and may include a double bond, an aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; cyclopentane; and the like.

[0100] The lithium salt may be used without any particular limitation as long as it is a compound capable of providing lithium ions used in a lithium secondary battery. Specifically, the anion of the lithium salt may be at least one selected from the following: - , Cl - Br - ,I - 、NO3 - 、N(CN)2 - 、BF4 -CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - and (CF3CF2SO2)2N - , and the lithium salt that can be used herein can be LiPF6, LiN(FSO2)2, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, LiB(C2O4)2, etc. The lithium salt concentration can preferably be used in the range of 0.1 to 5.0 M.

[0101] In order to improve the life characteristics of the battery, inhibit the decrease of the battery capacity, improve the discharge capacity of the battery, etc., the electrolyte may include additives in addition to the above-mentioned electrolyte components. For example, as additives, halogenated alkylene carbonate compounds such as difluoroethylene carbonate; pyridine; triethyl phosphite; triethanolamine; cyclic ethers; ethylenediamine; (condensed) glycol dimethyl ethers; hexamethylphosphoric triamide; nitrobenzene derivatives; sulfur; quinone imine dyes; N-substituted Oxazolidinone; N, N-substituted imidazolidine; ethylene glycol dialkyl ether; ammonium salt; pyrrole; 2-methoxyethanol; aluminum chloride; etc., but not limited thereto. The content of the additive may be 0.1 wt % to 10 wt %, preferably 0.1 wt % to 5 wt %, based on the total weight of the electrolyte.

[0102] (2) Activation step

[0103] Next, a step of charging and discharging the battery cell at least once under pressure to electrically activate the battery is performed. The activation step is a step of charging and discharging the battery cell to impart electrical properties and form a SEI (solid electrolyte interphase) film on the electrode to stabilize the battery.

[0104] In the present invention, the charging and discharging of the activation step is performed under pressure. At this time, the pressurization can be performed, for example, by mounting the battery cell on a fixture and then applying pressure to the battery cell via the fixture. In the case of a battery cell using a lithium-rich manganese-based oxide, excess gas is generated during the activation step. If the gas discharge is not smooth, lithium precipitation may be caused due to gas entrapment, or uneven activation may occur, which may lead to degradation of battery performance. Therefore, in the present invention, the activation step is performed under pressure to prevent gas entrapment in the entire battery cell and to allow the electrolyte to be properly impregnated, which enables the Li2MnO3 phase to be uniformly activated at a high voltage, thereby preventing abnormal behavior during battery operation.

[0105] On the other hand, the pressurization may be performed at a pressure of 0.1 kgf to 10 kgf, preferably 0.1 kgf to 8 kgf, and more preferably 0.2 kgf to 7 kgf. When the pressurization pressure condition satisfies the above range, damage to the battery cell can be prevented, and the effects of improving gas emission and electrolyte impregnation performance are more excellently exhibited.

[0106] On the other hand, in the present invention, if necessary, the activation step can be performed while changing the pressurization pressure. For example, in the initial stage of charging in the activation stage (e.g., below SOC 20), pressurization is performed at a relatively low pressure to ensure that the electrolyte is present in large quantities at the electrode interface, so that the SEI film can be stably formed. At a point when the amount of gas generated by film formation increases (e.g., after SOC 20), charging can be performed while increasing the pressurization pressure to remove the gas from the electrode interface. Charging can be performed at a relatively high pressurization pressure. When the activation step is performed while changing the pressurization pressure in this way, the gas discharge effect can be maximized while minimizing deformation or damage to the battery cell caused by pressurization, and charging can be performed at a relatively high current rate, so that the effect of reducing the activation step time can be obtained.

[0107] More specifically, the activation step may include charging at a pressurized pressure P1 until the SOC of the battery cell reaches 10 to 20, and then charging and discharging at a pressurized pressure P2. At this time, it is preferred that P1 and P2 satisfy the conditions of the following mathematical formula (1).

[0108] Mathematical formula (1): 5P1 ≤ P2 ≤ 15P1

[0109] When P1 and P2 satisfy the condition of mathematical formula (1), the gas discharge effect can be maximized, and charging can be performed at a relatively high current rate, which has the effect of reducing the activation step time.

[0110] On the other hand, the present invention is characterized in that charging is performed in a constant current mode until the charging cutoff voltage during the charging in the activation step, and then charging is performed in a constant voltage mode. As described in the present invention, charging is performed in a constant current-constant voltage mode, so that the unactivated Li2MnO3 phase can be minimized, thereby preventing abnormal behavior during battery operation.

[0111] In one example of the activation step, the battery is charged from SOC 60 to SOC 100 in a constant current mode and then charged in a constant voltage mode, wherein the charge cutoff current rate may be 0.01 C to 0.5 C or 0.06 C to 0.5 C when charged in the constant voltage mode.

[0112] On the other hand, in another example of the activation step, when charging in the constant voltage mode, the charge cutoff current rate may be 0.01 C to 0.15 C, preferably 0.03 C to 0.10 C, and more preferably 0.03 C to 0.06 C. If the charging in the constant voltage mode is terminated too early, the activation may not be sufficiently performed, and if the charging in the constant voltage mode is terminated too late, the time of the activation step may increase, and the manufacturing speed may decrease.

[0113] In addition, the charge cutoff voltage during charging may be greater than 4.35 V, for example, 4.4 V to 4.8 V, 4.4 V to 4.7 V, 4.4 V to 4.6 V, or 4.5 V to 4.6 V. If the charge cutoff voltage is 4.35 V or less, Li2MnO3 is not sufficiently activated, which makes it difficult to achieve high capacity, and abnormal behavior of capacity increase may occur during battery operation.

[0114] On the other hand, it is preferred to perform constant current charging to include at least a portion of the potential plateau interval (4.4 V to 4.6 V). In the case of a battery using a lithium-rich manganese oxide, a potential plateau interval in which the voltage is relatively constant and maintained in the voltage range of 4.4 V to 4.6 V will appear in the voltage distribution according to the charging rate. When charging is performed to include at least a portion of the potential plateau interval during constant current charging, the lithium-rich manganese oxide is activated, so that high capacity characteristics can be achieved. If the potential plateau interval is not included during activation charging, the Li2MnO3 phase is not fully activated, so the capacity increase effect is slight, and abnormal behavior may occur during cycling.

[0115] More specifically, the charge cutoff voltage may be set to satisfy the following mathematical formula (2).

[0116] Mathematical formula (2): 0.5A ≤ B ≤ A

[0117] Among them, in mathematical formula (2),

[0118] A is the area of ​​the charge curve in the voltage range of 4.3 V to 4.6 V in the dQ / dV graph obtained by differentiating a graph of the voltage V measured while the battery cell is charged to 4.6 V versus the battery charge capacity Q,

[0119] B is the charging curve area in the range from 4.3 V to the charging cutoff voltage in the dQ / dV graph obtained by differentiating a graph of the voltage V measured while charging the battery cell to the charging cutoff voltage in the activation step and the battery charging capacity Q.

[0120] When the charge cutoff voltage during activation charge is set to satisfy mathematical formula (2), high voltage activation is fully performed, so that the capacity can be excellently exhibited, and abnormal behavior caused by uneven activation of the Li2MnO3 phase can be more effectively suppressed.

[0121] On the other hand, if necessary, charging may include two or more steps with different charging speeds. For example, charging may include a first charging step of constant current charging at a first current rate, and a second charging step of constant current charging at a second current rate different from the first current rate, followed by constant voltage charging.

[0122] At this time, the first current rate and the second current rate may be independently 0.1 C to 1.0 C, or 0.1 C to 0.8 C, or 0.2 C to 0.8 C, or 0.3 C to 0.6 C. Preferably, the first current rate may be less than the second current rate. That is, the first charging step may be performed at a relatively low speed, and the second charging step may be performed at a relatively high speed. If the current rate in the first charging step is fast, the SEI film may be unstably formed on the electrode surface. If the SEI film is unstably formed on the electrode surface, the SEI film is easily decomposed during the operation of the battery, resulting in rapid degradation of the electrode, which may significantly reduce the life characteristics. However, if the charging rate is too slow, there is a problem that the time of the entire activation step is increased and the manufacturing speed is reduced. However, as in the present invention, in the first charging step as the initial stage of charging when the SEI film is formed, charging is performed at a low speed, and in the second charging step after the SEI film is formed to a certain extent, charging is performed at a high speed, so that the time of the entire activation step can be reduced while stably forming the SEI film on the electrode surface.

[0123] On the other hand, the first charging step may be performed until the SOC of the battery cell reaches 30 to 60. When the charging capacity in the first charging step satisfies the above range, a strong and dense SEI film is formed on the electrode surface, thereby achieving excellent life characteristics.

[0124] On the other hand, if necessary, the first charging step may be performed in two or more steps at different rates. For example, the first charging step may include a 1-1 charging step of charging the battery cell at a C rate of 0.1 C to 0.3 C and a 1-2 charging step of charging the battery cell at a C rate of 0.3 C to 1.0 C. At this time, the 1-1 charging step may be performed from SOC 0 to SOC3~5, and the 1-2 charging step may be performed from SOC 3~5 to SOC 30~60. When the first charging step is performed in two steps as described above, the charging rate can be kept low in the initial stage of SEI film formation, thereby forming a more solid and dense SEI film, and then by increasing the charging rate, oxygen desorption and cation mixing can be suppressed, and the time required for the activation step can be reduced.

[0125] On the other hand, the second charging step is preferably performed after the first charging step, that is, from SOC 30 to 60 to SOC 90 to 100. When the charging capacity in the second charging step satisfies the above range, the incomplete formation of the SEI film can be suppressed, and Li2MnO3 can be fully activated, thereby effectively preventing abnormal behavior during battery operation.

[0126] The second charging step is performed in a constant current-constant voltage mode, and the current rate (C rate) during constant current charging may be 0.1C to 1.0C, more preferably 0.3C to 0.8C, and more preferably 0.3C to 0.6C.

[0127] Next, the charged battery cell is discharged. At this time, the discharge can be performed at a C rate of 0.1 C to 1 C, preferably 0.3 to 1 C. On the other hand, the discharge can be performed in a constant current mode (CC mode), and the discharge cut-off voltage can be 2.0V to 3.0V.

[0128] On the other hand, the activation step is preferably performed under a temperature condition of 25° C. to 70° C., preferably 30° C. to 60° C., more preferably 40° C. to 50° C. When the activation step is performed within the above temperature range, Li2MnO3 is properly activated, thereby being able to achieve high capacity.

[0129] On the other hand, although not essential, the activation step may further include an aging step if desired. The aging step allows the electrolyte to be uniformly impregnated into the electrode assembly and stabilizes the battery, and may be performed before, during, and / or after discharge, and may be performed one or more times.

[0130] The aging step may be performed at, for example, 20 to 60° C., 20 to 50° C., preferably 30 to 50° C. When aging is performed at the above temperature, electrolyte impregnation and lithium mobility are improved, so that activation can be performed more smoothly.

[0131] Hereinafter, the present invention will be described in more detail with reference to specific examples.

[0132] Example 1

[0133] The positive electrode active material: conductive material: PVDF binder were mixed in N-methylpyrrolidone at a weight ratio of 97:1:2 to prepare a positive electrode slurry. 1.38 [Ni 0.363 Co 0.005 Mn 0.642 ]O2 is used as the positive electrode active material, and CNT is used as the conductive material. The positive electrode slurry is coated on an aluminum current collector sheet, dried and rolled to manufacture the positive electrode.

[0134] The negative electrode active material: conductive material: binder were mixed in water at a weight ratio of 96:1:3 to prepare a negative electrode slurry. At this time, graphite was used as the negative electrode active material, carbon black was used as the conductive material, and SBR and CMC as the binder were mixed at a weight ratio of 2:1 and used. The negative electrode slurry was applied to a copper current collector sheet, dried and rolled to manufacture a negative electrode.

[0135] The separator is inserted between the positive electrode and the negative electrode manufactured as above to manufacture an electrode assembly, and the electrode assembly is inserted into a battery case, and then an electrolyte is injected, thereby manufacturing a battery cell.

[0136] The battery cell was mounted on the jig and charged to 4.6 V at 0.3 C constant current mode, and then changed to constant voltage mode for charging. When the current reached 0.05 C, the charging was terminated. Then, the charged battery cell was discharged to 2.0 V at a constant current of 0.5 C, and then the battery cell was removed from the jig. On the other hand, during charging, the charging was carried out at a constant current of 0.5 kgf / cm 2 The pressure was increased from SOC 0 to SOC 17, and then the clamp was adjusted and the pressure was increased at 5 kgf / cm 2 The pressure is increased while charging and discharging.

[0137] Example 2

[0138] A battery cell was manufactured in the same manner as in Example 1, mounted on a fixture, and then charged to SOC 60 in a 1.0 C constant current mode (first charging step). Then, the battery cell was charged to 4.6 V in a 0.4 C constant current mode, and then changed to a constant voltage mode for charging. When the current reached 0.05 C, the charging was terminated (second charging step). Then, the charged battery cell was discharged to 2.0 V at a constant current of 0.5 C, and then the battery cell was removed from the fixture. On the other hand, during the above-mentioned charging, the charging was carried out at a constant current of 0.5 kgf / cm 2 The pressure was increased from SOC 0 to SOC 17, and then the clamp was adjusted and the pressure was increased at 5 kgf / cm 2 The pressure is increased while charging and discharging.

[0139] Example 3

[0140] A battery cell was manufactured in the same manner as in Example 1, mounted on a jig, and then charged to 4.5 V in a 0.3 C constant current mode, and then changed to a constant voltage mode for charging. When the current reached 0.05 C, the charging was terminated. Then, the charged battery cell was discharged to 2.0 V at a constant current of 0.5 C, and then the battery cell was removed from the jig. On the other hand, during the above-mentioned charging, the charging was carried out at a constant current of 0.5 kgf / cm 2 The pressure was increased from SOC 0 to SOC 17, and then the clamp was adjusted and the pressure was increased at 5 kgf / cm 2 The pressure is increased while charging and discharging.

[0141] Comparative Example 1

[0142] A battery cell was manufactured in the same manner as in Example 1, mounted on a jig, and then charged to 4.6 V in a 0.3 C constant current mode, and then changed to a constant voltage mode for charging. When the current reached 0.05 C, the charging was terminated. Then, the charged battery cell was discharged to 2.0 V at a constant current of 0.5 C.

[0143] Comparative Example 2

[0144] A battery cell was manufactured in the same manner as in Example 1, mounted on a jig, and then charged to SOC 60 in a 1.0 C constant current mode. Then, the battery cell was charged to 4.6 V in a 0.4 C constant current mode. Then, the charged battery cell was discharged to 2.0 V at a constant current of 0.5 C, and then the battery cell was removed from the jig. On the other hand, during the above-mentioned charging, the battery cell was charged at a constant current of 0.5 kgf / cm 2The pressure was increased from SOC 0 to SOC 17, and then the clamp was adjusted and the pressure was increased at 5 kgf / cm 2 The pressure is increased while charging and discharging.

[0145] Comparative Example 3

[0146] A battery cell was manufactured in the same manner as in Example 1, mounted on a jig, and then charged to 4.35 V in a 0.3 C constant current mode, and then changed to a constant voltage mode for charging. When the current reached 0.05 C, the charging was terminated. Then, the charged battery cell was discharged to 2.0 V at a constant current of 0.5 C, and then the battery cell was removed from the jig. On the other hand, during the above-mentioned charging, the charging was carried out at a constant current of 0.5 kgf / cm 2 Then adjust the clamp and pressurize the pressure at 5 kgf / cm 2 The pressure is increased while charging and discharging.

[0147] Comparative Example 4

[0148] A battery cell was manufactured in the same manner as in Example 1, mounted on a jig, and then charged to 3.9 V in a 0.3 C constant current mode, and then changed to a constant voltage mode for charging. Then, the charged battery cell was discharged to 2.0 V at a constant current of 0.5 C, and then the battery cell was removed from the jig. On the other hand, during the above-mentioned charging, the charging was carried out at a constant current of 0.5 kgf / cm 2 The pressure was increased from SOC 0 to SOC 17, and then the clamp was adjusted and the pressure was increased at 5 kgf / cm 2 The pressure is increased while charging and discharging.

[0149] Experimental Example 1

[0150] During the activation step of Examples 1 to 3 and Comparative Examples 1 to 4, the capacity based on voltage was measured during the charging process to obtain a voltage-capacity graph, and the voltage-capacity graph was differentiated to obtain a dQ / dV graph.

[0151] Then, the percentages of the charge curve areas in the voltage range of 4.3 V to 4.6 V shown in the dQ / dV graph of Example 2 and Comparative Examples 1 to 4 were measured based on the charge curve areas in the voltage range of 4.3 V to 4.6 V shown in the dQ / dV graph of Example 1. The measurement results are shown in [Table 1] below.

[0152]

[0153] Experimental Example 2: Initial Capacity

[0154] The lithium secondary battery activated according to the method of Examples 1 to 3 and Comparative Examples 1 to 4 was charged to 4.35 V at 0.33 C in a constant current-constant voltage mode at 25°C, and then cut off when the current reached 0.05 C. Then, the battery was discharged to 2.0 V at a constant current of 0.33C to measure the initial discharge capacity. When the initial discharge capacity of the lithium secondary battery of Example 1 was set to 100%, the relative ratio of the initial discharge capacity of the lithium secondary batteries of Example 2 and Comparative Examples 2 to 4 was measured. The measurement results are shown in [Table 2] below. On the other hand, Li precipitation occurred in the lithium secondary battery activated by the method of Comparative Example 1, so the battery could not work.

[0155]

[0156] As shown in [Table 2], the lithium secondary batteries of Examples 1 to 3 activated by charging to a voltage of 4.3 V or more in a constant current-constant voltage mode while applying pressure using a clamp exhibited an initial capacity superior to that of Comparative Examples 1 to 4. On the other hand, it can be confirmed that the lithium secondary battery of Comparative Example 1 activated without pressurization cannot work due to lithium plating. When charging only in a constant current mode instead of a constant current-constant voltage mode (Comparative Example 2), or when activated at a charge cutoff voltage of 4.35 V or less (Comparative Examples 3 and 4), the initial discharge capacity decreases even if a pressurization process is included.

[0157] Experimental Example 3: High Temperature Life Characteristics

[0158] The activated lithium secondary batteries activated according to the methods of Examples 1 to 3 and Comparative Examples 1 to 4 were charged to 4.35 V (cut-off current 0.05 C) at 0.33 C in a constant current-constant voltage mode at 45°C, and then discharged to 2.0 V at a constant current, which was set as one cycle. After 50 charge and discharge cycles, the capacity retention rate and voltage drop were measured. The measurement results are shown in FIG. Figure 1 as shown in .

[0159] On the other hand, in the lithium secondary battery activated by the method of Comparative Example 1, Li deposition occurred, and thus the battery did not operate.

[0160] like Figure 1 As shown in , the lithium secondary batteries activated by the methods of Examples 1 to 3 maintained a constant capacity during 50 cycles of charge and discharge and did not significantly increase the voltage drop, while the lithium secondary batteries activated by the methods of Comparative Examples 2 to 4 showed abnormal operation, in which the capacity increased with increasing cycles and the voltage drop increased significantly.

[0161] Industrial Applicability

[0162] In the method for manufacturing a lithium secondary battery according to the present invention, an activation step is performed under pressure and charging is performed in a constant current-constant voltage mode, thereby promoting gas emission, minimizing unactivated Li2MnO3 phases, and preventing lithium precipitation and abnormal behavior during battery operation.

Claims

1. A method for manufacturing a lithium secondary battery, the method comprising the following steps: Preparing a battery cell including a positive electrode, a negative electrode, and an electrolyte, wherein the positive electrode contains a lithium-rich manganese-based oxide, wherein the content of manganese is greater than 50 mol% relative to all metals other than lithium, and the molar ratio of lithium to all metals other than lithium (Li / Me) is greater than 1; And Activating by charging and discharging the battery cell while applying pressure to the battery cell, wherein in the activation step, charging is performed in a constant current mode until a charging cut-off voltage, and then charging is performed in a constant voltage mode, and the charging cut-off voltage is greater than 4.35 V.

2. The method for manufacturing a lithium secondary battery according to claim 1, wherein: The charging in the constant current mode is performed to include at least a part of the potential plateau region.

3. The method for manufacturing a lithium secondary battery according to claim 1, wherein: The lithium-rich manganese-based oxide is represented by the following Chemical Formula 1, [Chemical Formula 1] Li a Ni b Co c Mr d M e O2 wherein, in Chemical Formula 1, 1 < a, 0 ≤ b ≤ 0.5, 0 ≤ c ≤ 0.1, 0.5 ≤ d < 1.0 and 0 ≤ e ≤ 0.2, M is at least one selected from Al, B, Co, W, Mg, V, Ti, Zn, Ga, In, Ru, Nb, Sn, Sr, and Zr.

4. The method for manufacturing a lithium secondary battery according to claim 3, wherein: In Chemical Formula 1, 1.1 ≤ a ≤ 1.5, 0.1 ≤ b ≤ 0.4, 0 ≤ c ≤ 0.05, 0.5 ≤ d ≤ 0.80 and 0 ≤ e ≤ 0.

1.

5. The method for manufacturing a lithium secondary battery according to claim 1, wherein: The cut-off current during charging in the constant voltage mode is 0.01 C to 0.5 C.

6. The method for manufacturing a lithium secondary battery according to claim 5, wherein: In the activation step, charging in the constant current mode is performed from SOC 60 to SOC 100.

7. The method for manufacturing a lithium secondary battery according to claim 1, wherein: In the activation step, the charging includes: A first charging step: performing constant current charging at a first current rate, and A second charging step: performing constant current charging at a second current rate different from the first current rate, and then performing constant voltage charging.

8. The method for manufacturing a lithium secondary battery according to claim 7, wherein: The first current rate and the second current rate are each independently 0.1 C to 1.0 C.

9. The method for manufacturing a lithium secondary battery according to claim 7, wherein: The first charging step is performed from SOC 30 to SOC 60, and The second charging step is performed from SOC 30 - 60 to SOC 90 - 100.

10. The method for manufacturing a lithium secondary battery according to claim 1, wherein: The activation step is performed while mounting the battery cell on a fixture and applying pressure to the battery cell.

11. The method for manufacturing a lithium secondary battery according to claim 1, wherein: The activation step is performed while changing the pressing pressure.

12. The method for manufacturing a lithium secondary battery according to claim 1, wherein: The activation step includes: charging at a pressurized pressure P1 until the SOC of the battery cell reaches 10 to 20, and then charging and discharging at a pressurized pressure P2.

13. The method for manufacturing a lithium secondary battery according to claim 12, wherein: The pressurization pressure P1 and the pressurization pressure P2 satisfy the following mathematical formula (1): Mathematical formula (1): 5P1 ≤ P2 ≤ 15P1.

14. The method for manufacturing a lithium secondary battery according to claim 1, wherein: When the charging curve area in the voltage range of 4.3 V to 4.6 V in the dQ / dV graph obtained by differentiating the graph of the voltage V measured while charging the battery cell to 4.6 V and the battery charge capacity Q is represented as A, and the charging curve area in the range of 4.3 V to the charging cut-off voltage in the dQ / dV graph obtained by differentiating the graph of the voltage V measured while charging the battery cell to the charging cut-off voltage of the activation step and the battery charge capacity Q is represented as B, the following mathematical formula (2) is satisfied: Mathematical formula (2): 0.5A ≤ B ≤ A.